ORIENTASI HYBRID LEARNING MELALUI MODEL HYBRID LEARNING DENGAN BANTUAN MULTIMEDIA DI DALAM KEGIATAN PEMBELAJARAN - Ino Angga Putra (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2015)
The development of information and communication technologies have an impact on changes in the field of education where one student and teacher interaction. It allows the distance learning with the use of technology, information, and communication. Utilization of ICT which can affect students' reactions to the active and communicative in learning so increased student learning outcomes. However, the fact that the use of ICT is still less than the maximum advance in the use of multimedia. In response, alternative solutions are needed that can exploit the use of ICT in the classroom. One of them is the implementation of learning with hybrid learning where learning becomes varied, interactive and communicative. Hybrid learning combines face-to-face learning with the use of technology, information, and communication. The discussion will be directed to the implementation of the hybrid learning through a hybrid learning models with the help of multimedia. KEYWORD: hybrid learning, hybrid learning models, multimedia